2014
DOI: 10.1177/0961203313518623
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders and systemic lupus erythematosus

Abstract: Sleep disorders appear to occur in more than half of patients with SLE and appear to be associated with disease activity. Pain and fatigue are also related to sleep disorders. Among the hypotheses on the possible mechanisms underlining the association between sleep disorders and SLE, psychosocial/psychological factors, especially depression, were the most frequently reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
3
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 51 publications
6
85
3
6
Order By: Relevance
“…In health‐related quality of life, we found very similar results, as obtained in the Spanish validation of LupusQoL, emotional health and burden to others being the most affected domains . The differences in fatigue and mood between SLE patients and healthy controls also were congruent with previous studies in which the patients were showing higher levels of fatigue, anxiety and depression than healthy participants . The difference in perceived stress was not statistically significant; however, a P ‐value close to significance (0.79) was found.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In health‐related quality of life, we found very similar results, as obtained in the Spanish validation of LupusQoL, emotional health and burden to others being the most affected domains . The differences in fatigue and mood between SLE patients and healthy controls also were congruent with previous studies in which the patients were showing higher levels of fatigue, anxiety and depression than healthy participants . The difference in perceived stress was not statistically significant; however, a P ‐value close to significance (0.79) was found.…”
Section: Discussionsupporting
confidence: 89%
“…We found that SLE patients reported poorer sleep quality, as shown in the differences in PSQI scores with regard to the healthy sample in subjective sleep quality, sleep latency, sleep duration, sleep disturbance, use of sleeping medication, daytime dysfunction and the PSQI global index. These results are similar to those obtained in other studies, for example in the review of Palagini et al ., in which more than half of their SLE patients had sleep problems, an increased sleep latency, more awakenings during the night and lower sleep efficiency than a healthy population …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the pain of SLE patients may have significant physical and psychological impacts on them. For example, research has found the higher the pain levels, the worse the sleep and fatigue perceived by patients (Palagini et al, 2014). Pain may also result in the problem of depression (Figueiredo-Braga et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%